Enhancement of probiotic survival in low pH and bile salt condition using alginate-hi-maize starch encapsulation - Ngov, Sina; Sukboonyasatit, Duljira; Paseephol, Tatdao (Asia-Pacific Journal of Science and Technology, 2017)
There has been an increased interest in foods-containing probiotics over the past few decades. To provide health benefits to consumers, probiotics must survive in food during storage and during transit through the gastrointestinal tract. In this study, the encapsulated probiotic bacteria were tested in comparison with free cells for their acid and bile tolerance. Two probiotic strains, i.e. Lactobacillus casei TISTR 1463 (LC 1463) and Lactobacillus acidophilus TISTR 1338 (LA 1338) were separately encapsulated with calcium alginate and co-encapsulated with 0-3% Hi-maize starch using extrusion method. The acid tolerance of probiotics was examined in acidified MRS broth at pH 2, 4 and 65 OVER a 3-h incubation period. Bile tolerance was tested using 0.5 or 1% bile salt in MRS broth over a 3-h of incubation. The results showed that co-encapsulation with 2% Hi-maize starch enhanced the viability of both probiotic strains in acid. For LC 1463, viability of co-encapsulated bacteria decreased by 1.62 log CFU/ml after 3-h of incubation at pH 2, while 3.9 log CFU/ml and 4.5 log CFU/ml were lost in the encapsulated and free cells, respectively. For LA 1338, there was a 2.06 log CFU/ml reduction in viability of co-encapsulated bacteria after 3-h exposure to pH 2, compared with the decrease by 2.6 log CFU/ml and 4.2 log CFU/ml in encapsulated and free cells, respectively. However, at pH 4 and 6.5 no significant difference in the reduction of viable count was found between free and encapsulated cells. Similar results were obtained in bile salt tolerance test. Co-encapsulated LC 1463 survived better than other samples, showing only 1.4 log CFU/ml reduction after exposure to 1% bile salt for 3 h. Under the same condition, the viability reduction of free and encapsulated cells was 3.7-4.7 log CFU/ml. For LA 1338, co-encapsulated bacteria survived with a loss of 2.2 log CFU/ml, compared to 4.75-4.84 log CFU/ml loss with free and encapsulated cells. Overall, encapsulation with alginate-starch could be a useful method for maintaining the viability of probiotics in acidic foods and for improving the bacterial delivery to the human gut.